Homines, funera, astra 2 life beyond death in ancient times : (Romanian case studies) : proceedings of the International Symposium on Funerary Anthropology 23-26 September 2012, '1 Decembrie 1918' University (Alba Iulia, Romania) - Kogălniceanu, Raluca 1977-; Gligor, Mihai 1971-; Curcă, Roxana-Gabriela 1978-; Stratton, Susan (Archaeopress Publishing Ltd, 2015)
The present volume reunites most of the papers that were presented at the second meeting of the Homines, Funera, Astra Symposium on Funerary Anthropology that took place at '1 Decembrie 1918' University, Alba Iulia, between 23rd and 26th September 2012. The theme of the volume is life beyond death in ancient times